A Study Of Air System Performance On EMU KTM KTM Class 83 - ROSLI, NIK NURUL SYAFIQA; YAHYA, MUSLI NIZAM; MOHD ALI, MOHD TAUFIK (Progress in Engineering Application and Technology, 2023)
The air system plays a crucial role in ensuring the safe and efficient operation of the train by facilitating various functions, including brake pipe system, pantograph system, door system, suspension system and more. However, instances of failure in the air system can result in significant disruptions to train services and pose potential safety risks to passengers. This research analyse the Electric Multiple Unit (EMU) air system failure and recommends suggestion to optimise train performance. This research examines failure analysis of air system with 20 set of EMU train from 2020 to 2022 at EMU Sentul Depot. Damage to the train air system can compromise infrastructure safety and longevity. From the data failures that has been analyse, the result showed that the main reservoir dropped had the highest failure rate. The research found that improving EMU component quality before operation, identifying important train system maintenance components, and optimising the train maintenance cycle can reduce failure severity.